Community engagement in mobile and hard-to-reach populations: a community-based intervention for malaria elimination in a tri-national region of the Guiana Shield - Jimeno-Maroto, Irene; Galindo, Muriel Suzanne; Miller, Jane Bordalo; Lambert, Yann; Carboni, Carlotta; Bardon, Teddy; Plessis, Lorraine; Vreden, Stephen; Suarez-Mutis, Martha; Douine, Maylis; Sanna, Alice (Frontiers in Public Health, 2024)
Several countries of the Guiana Shield are aiming at the control and elimination of malaria in areas where Artisanal and Small-scale Gold Mining (ASGM) activities predominate, raising questions about how to strengthen community engagement to improve the effectiveness of health programs. The Curema project focuses its intervention on the mobile and hard-to-reach ASGM population, complementing the efforts of national programs in the Guiana Shield. The Curema intervention combines targeted drug administration for suspected Plasmodium vivax asymptomatic carriers, the Malakit distribution, and health education activities.The primary goals of this manuscript are to outline a pathway to foster community participation in the Curema project aimed at eliminating malaria. Thus, it presents a vision of the challenges that the AGSM community poses in terms of community participation for an asymptomatic problem; and highlights the community-based model and the Information, Education and Communication (IEC) components as foundations for participation. In addition, it also presents culturally sensitive IEC strategies designed through iterative and collaborative consultative processes and other bottom-up outreach activities.The community engagement approach facilitates adaptability and responsiveness in a complex, evolving context increasing the effectiveness of interventions.